2-(3,4-Dichlorophenyl)-N-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)acetamide - Mahan, Aneeka (International Union of Crystallography, 2013)
In the title compound, C(19)H(17)Cl(2)N(3)O(2), there are three molecules (A, B and C) in the asymmetric unit and each differs in the conformation adopted. As a result of steric repulsion, the amide group is rotated with respect to both the dichlorophenyl and 2,3-dihydro-1H-pyrazol-4-yl rings, making dihedral angles of 44.5 (2) and 56.2 (2)°, respectively in A, 51.1 (2) and 54.1 (2)° in B, and 53.8 (2) and 54.6 (2)° in C. The dihedral angles between the dichlorophenyl and 2,3-dihydro-1H-pyrazol-4-yl rings are 54.8 (2), 76.2 (2) and 77.5 (2)° in molecules A, B and C, respectively, while the 2,3-dihydro-1H-pyrazol-4-yl and phenyl rings make dihedral angles of 45.3 (2), 51.2 (2) and 42.8 (2)°, respectively. In the crystal, two of the molecules are linked through N—H⋯O hydrogen bonding to an adjoining molecule, forming dimers of the R (2) (2)(10) type, while the third molecule forms such dimers with itself. C—H⋯O interactions link the dimers.